228k views
5 votes
Find z1z2 if z1 = 3(cos37° + isin37°) and z2 = 2/3(cos53° + isin53°).

User StrubT
by
6.1k points

2 Answers

4 votes

Answer:


z_(1)\cdot z_(2) = 2\cdot (\cos 90^(\circ) + i \cdot \sin 90^(\circ))

Explanation:

Both variable can be rewritten into polar form:


z_(1) = 3\cdot e^(i\cdot 0.205\pi) and
z_(2) = (2)/(3)\cdot e^(i\cdot 0.294\pi)

The complex product is equal to:


z_(1)\cdot z_(2) = (3)\cdot \left((2)/(3)) \cdot e^(i\cdot (0.205\pi+0.294\pi))


z_(1)\cdot z_(2) = 2 \cdot e^(i\cdot 0.499\pi)}

The resultant expression in rectangular form is:


z_(1)\cdot z_(2) = 2\cdot (\cos 90^(\circ) + i \cdot \sin 90^(\circ))

User Webaholik
by
5.0k points
2 votes

Answer:

The correct question is:

Find
z_(1).z_(2) if
z_(1)= 3(cos37 + isin37) and
z_(2)= (2)/(3) (cos53 + isin53).

(Note: the angles mentioned in the equations above are in degrees)

The answer is
z_(1).z_(2)= 2i

Explanation:


z_(1).z_(2)= 3(cos37 + isin37)* (2)/(3) (cos53 + isin53)


z_(1).z_(2)= (3cos37 + 3isin37)* ((2)/(3) cos53 + (2)/(3)isin53)


z_(1).z_(2)= 3cos37*(2)/(3) cos53 + 3cos37*(2)/(3)isin53+3isin37*(2)/(3) cos53+3isin37*(2)/(3)isin53


z_(1).z_(2)= 0.961+1.275i+0.724i-0.961 (Because
i*i=i^(2)=-1 &
i=√(-1))


z_(1).z_(2)= 0.961+1.275i+0.724i-0.961


z_(1).z_(2)= 2i

User Barclay
by
5.3k points